NEW INFORMATION ABOUT KARSHI SARDOB (TAMADDUN NURI JURNALI, 2024)
The article presents new information related to the history of the construction of cisterns, which are considered a unique technical water structure located in the Karshi oasis in the western part of Southern Sogd. Cisterns were considered a complex engineering structure on trade and caravan routes, in places with a shortage of drinking water, in desert areas and the great achievements of our ancestors in science, thinking, architecture, climatic conditions, natural geography, soil and human activity. knowledge. It has been established that 12 such structures are located in the desert area of ​​the Karshi oasis, around the branches of the Great Silk Road, on lands where there is a shortage of drinking water.